Antihypertensive effects of Ma-kiang fruit extract on hypertensive rats - คำแก้ว ณฐกร; ผจญภัย วาทิตา; รมสาร ศศิวิมล; เขียวสีมา ปภาอร; พิทักษ์พล วาสนา; ชูทิพย์ กรองกาญจน์ (Health Science, Science and Technology Reviews, 2019)
The aim of this study was to investigate the acute and chronic effects of Ma-kiang fruit extract on blood pressure in L-NAME induced hypertensive rats. We found significant reduction of blood pressure in a dose-dependent manner through intravenous injection of the extract (20, 40 and 60 mg/kg). Moreover, the chronic oral administration of the extract (500 mg/kg/day) for 6 weeks in hypertensive rats showed the significant attenuation of hypertension, and did not significantly decreased heart rate.